Assessment of Yield Limiting Nutrients through Response of Rice to Nutrient Omission Technique of Shallow Brown Terrace under Madhupur Tract - Iqbal, Mosud; Jahan, Afsana; Islam, A B M Jamiul; Islam, Tanjina; Islam, Aminul (European Journal of Applied Sciences, 2023)
A field experiment was conducted during Boro 2018-2019 and T.Aman 2019 season at Bangladesh Rice Research Institute, Gazipur to assess the yield limiting nutrients and response of rice to nutrient omission technique for the Boro-Fallow-T. Aman rice cropping pattern. The experiment was set up in a split plot design (RCBD) with three replications. Four fertilizer treatments viz T1=NPK (AEZ basis), T2=N omission (-N), T3=P omission (-P) and T4=K omission (-K) were imposed in the main plots. The rice genotypes viz Nerica Mutant, BRRI dhan28 and BRRI dhan45 in Boro season and in T.Aman BRC245-4-19-2-1, BR11 and BRRI dhan31 was laid in the subplots. Interaction of nutrient omission and rice genotypes showed significant effect on all the tested growth attributes in Boro 2018-19 season. Treatments with ample dose (NPK) show significantly outperformed than N and P omission in respect of the plant height, tiller and panicle number per square meter but no significance differences of growth attributes were observed in case of K omission in Boro season. Varietal influence of different rice genotypes due to ample dose of NPK and their omissions were insignificant but significance influence of grain yield due to nutrient omission was found. Due to P omission, highest yield reduction (80%, BRRI dhan45) was recorded in Boro season. In T.Aman Season, Only N omission significantly produced lowest tiller and panicle number per meter square. Less than 25% of yield reductions due to nutrient omission were recorded in T.Aman season. The overall findings of the study point out that the yield limiting nutrients in Boro season were identified as N and P. However, N and K was found yield limiting nutrient factor in T.Aman season.